Istiqamah Seumubeuet Teungku Dayah Salafiyah Aceh: (Analysis of the Alamtologi Approach) - Amiruddin Amiruddin; Warul Walidin; Syabuddin Gade; Silahuddin (Al-Fikrah, 2023)
Teungku dayah plays an important role in Acehnese society and is respected and followed wholeheartedly by the local community. One of the main reasons for this is because they carry out religious teachings with the principle of istiqamah. Istiqamah means striving uprightly and consistently, having a firm stance, patience in facing temptations, and consistency in actions and behaviors. This research is a literature study (library research) with a Alamtologi approach. The study found that to achieve balance or istiqamah, it is important to fulfill the needs and capacities required by all parties involved. This can be explained according to the Alamtology: XYZ Formula [The Hidden Formula] by Masa Bayu. For example, for a teacher to be istiqamah in teaching, the leadership or relevant institution must meet the needs or requests of the teacher. The needs referred to are those that are suitable for the individual teacher's requirements and do not have to be the same as other teachers' needs, as each individual has different needs according to their own requirements. On the other hand, teachers also need to meet the needs of the institution or organization where they work. Additionally, teachers also need to enhance their capacity through the development of knowledge, skills, and other relevant aspects.